Inter-linkages : synergies and coordination between multilateral environmental agreements (United Nations University TokyoJP, 1999)
Looks at practical steps that can be taken to more effectively utilize the natural synergies within our environment, as they may hold the key to better integrated, effective and efficient coordination between different multilateral environment agreements.
Keywords: INTERNATIONAL AGREEMENTS